If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -1(8 + -1y) = -20 Y + (8 * -1 + -1y * -1) = -20 Y + (-8 + 1y) = -20 Reorder the terms: -8 + Y + 1y = -20 Solving -8 + Y + 1y = -20 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + Y + 8 + 1y = -20 + 8 Reorder the terms: -8 + 8 + Y + 1y = -20 + 8 Combine like terms: -8 + 8 = 0 0 + Y + 1y = -20 + 8 Y + 1y = -20 + 8 Combine like terms: -20 + 8 = -12 Y + 1y = -12 Add '-1y' to each side of the equation. Y + 1y + -1y = -12 + -1y Combine like terms: 1y + -1y = 0 Y + 0 = -12 + -1y Y = -12 + -1y Simplifying Y = -12 + -1y
| 2a+3=-11 | | 15+8-12=x | | 12x+2=3x+11 | | 16x-18+6x+4=118 | | 32+8v=8(7v-2) | | -8=23-5q | | f(x)=5x^2-7x^3 | | -3-6x^2=-103 | | 1+6p=1-p | | 5+a=29 | | (11t-s)(t+5s)= | | -10x+2=-10 | | -10x+2=-11 | | -12=8+f2 | | 14000=36000-1500t | | 1400=36000-1500t | | -20=-5n+-3n | | 35=1-2a | | -41=2x-7 | | -5(6y-9)-y=-2(y-4) | | 4(x-3)=6(x+1) | | -2(5x-1)=11 | | n^2+5=105 | | -7x+24=8+x | | (2b-5)(2b+5)= | | -3-8(3-2k)=-155 | | -2x^2=-76 | | 2.5(+-2)-6=9 | | 5x-5(2-2x)=-10 | | x-5+4=9 | | 2-6x=10-2x | | 10x+24(x-3)=336 |